TO THE QUESTION OF REFINING THE ACCOUNTING CLASSIFICATION OF INTANGIBLE ASSETS OF SCIENTIFIC ENTERPRISES - ROMANOVA, OLHA; HONCHAR, KSENIIA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The modern development of the economic system of our state requires the use of new scientific knowledge and innovations. The scientific sphere is a small segment of the economy in our country, as of 2020 the share of this industry in Ukraine’s GDP was only 3.04% and is much lower than this figure in Germany (6.24%), Spain (4.68%) ), Poland (5.92%) and France (8.44%). Science-intensive enterprises and intangible assets are interrelated, as the production capacity of enterprises in this industry depends on the availability of intellectual property rights. However, intangible assets are underestimated in the activities of Ukrainian science-intensive enterprises, and therefore today professional, scientific and technical activities (industry M) in the country is experiencing a crisis, which reduces the prestige of scientific work. The article considers the issues of approaches to the classification of intangible assets for accounting purposes. The main documents governing the accounting of intangible assets in our country are highlighted. Different approaches to the essence of intangible assets in scientific and regulatory sources are analyzed. It was found that intangible assets are one of the least studied categories in accounting. The share of the scientific sphere in GDP has been studied. The structure of investments in intangible assets of Ukrainian enterprises is analyzed. The importance of expenses for professional training, retraining and advanced training for innovative enterprises of the "M" branch is established. As a result, we concluded that the issue of classification of intangible assets remains unresolved, and therefore is relevant, and provided recommendations for improving the accounting and analytical management of knowledge-intensive enterprises.